METAPHORICAL MODEL «DAY → NAP» IN TIUTCHEV’S POETRY - Каменева, Ирина (SWorldJournal, 2021)
The article is devoted to the analysis of the linguistic representation of the concept “day” in the cognitive aspect. The novelty of the work is to analyze the metaphorical means that the poet uses to describe the day. The article analyzes the poetic tex